Spy who got away - "Wise, David" (London, 1988)
In spring 1983, Edward Howard was preparing for his first overseas posting as a CIA case officers tour in the agency's most sensitive station, Moscow. In June 1986, he became the first CIA officer to defect to the Soviet Union. Wise, a frequent writer on intelligence issues and co-author (with Thomas B. Ross) of The Invisible Government , interviewed Howard (in Budapest), his family, co-workers, and American counterintelligence officers to prepare this compelling analysis of events and mostly CIA bungles that led to a major U.S. intelligence disaster. The remarkable, clearly told story reveals intriguing snippets of the workings of American intelligence.
Keywords: Soviet anti - American espionage